Practical Implementation of Fiqh in Islamic Religious Education Learning at SMP Daarut Tauhiid Boarding School Putra - Haritsahrizal, Muhammad Zaid; Kosasih, Aceng; Fakhruddin, Agus (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2025)
This study analyzes the implementation of Fiqh practical learning in the Islamic Religious Education (PAI) curriculum at SMP Daarut Tauhiid Boarding School Putra. The research aims to investigate the design, supporting facilities, execution, and outcomes of Fiqh practical sessions, focusing on topics such as funeral rites. Employing a qualitative descriptive method, data were collected through interviews, observations, and document analysis involving teachers, administrators, and students. Findings indicate that the practical learning design integrates methods such as Problem-Based Learning (PBL), Project-Based Learning (PjBL), and Contextual Teaching and Learning (CTL), which bridge theory and real-life application. Resources like Safinatunnajah and Fathul Qorib serve as primary references, offering comprehensive theoretical support. The school facilitates practical sessions using mannequins and other tools, though challenges like inadequate facilities and the need for teacher adaptation persist. Students actively participated in learning, showcasing enthusiasm and demonstrating improved understanding of Fiqh practices. However, issues such as discipline and varying levels of student seriousness were noted. Despite these challenges, practical learning has proven effective in enhancing students’ cognitive, affective, and psychomotor competencies, making it a valuable pedagogical approach for character-building and religious education.